Fungsi Islamic Worlview dalam Kehidupan Seorang Muslim - Kurniawan, Ilham; Hakim, Lukmanul; Abdullah, Abdullah; Rohman, Abdul; Sumiran, Sumiran (Lembaga Yasin AlSys, 2026)
The phenomenon of value disorientation and identity crisis among contemporary Muslims, marked by the growing influence of materialism and secularization, indicates a gap between religious knowledge and the comprehensive implementation of the Islamic Worldview. This study aims to analyse in depth the essential functions of the Islamic Worldview as a foundation of thought, a shaper of character, and a guide to action for Muslims amid contemporary challenges. The study employs a literature review (library research) method by examining and synthesizing relevant scholarly sources on the concept and role of the Islamic Worldview. The findings identify six main functions of the Islamic Worldview, namely: (1) foundation of creed (tauhid); (2) moral and ethical guidance; (3) determinant of life purpose (attaining sa‘adah); (4) filter against external influences, particularly secularism; (5) basis for social and scientific action; and (6) integration of the worldly and hereafter dimensions. Accordingly, the Islamic Worldview is not merely a theoretical construct, but a comprehensive belief system that is vital for shaping the holistic Muslim personality (Insan Kamil). Proper internalization of the Islamic Worldview serves as a firm foundation for safeguarding identity, orienting life goals, and reinforcing the consistency of Muslim behaviour, thereby offering a conceptual solution to the global value crisis.